Factors That Influence the Event Diabetes Millitus at Sumbersari Bantul Hospital Metro City - Supardi Supardi; Sapti Ayubbana; Anik Inayati; Nia Risa Dewi (Malahayati Nursing Journal, 2025)
ABSTRACT Diabetes mellitus is a chronic disease that requires long-term medical treatment, by controlling blood sugar levels to cause diabetes complications. Diabetes is often referred to as the 'mother' of various diseases. The reason is, diabetes can be the cause of many disease complications, such as heart disease, kidney disease, eye disease, foot disease, nerve disease, stroke, hypertension and many others. To identify factors associated with the incidence of diabetes mellitus complicated by hypertension. The research design used was Cross Sectional. The population of this study was all Diabetes mellitus patients who came to visit Sumbersari Bantul Hospital, Metro City from January 15 to February 14 2024. The sample size was 40 respondents, determined using Total Sampling. Statistical tests use Chi Square (X2). This study concluded that there was a significant and meaningful relationship for the variables level of education (p value = 0.007) and (OR: 16.00), consumption patterns (p value = 0.035) and active smoking (p value = 0.027) with the incidence of Diabetes Militus who experience hypertension, while those that do not have a significant relationship are the variables age, gender, body mass index, genetics, physical activity, and sleep patterns with the incidence of Diabetes Militus who experience hypertension. Keywords: Smokers, Hypertension, Diabetes Mellitus,  ABSTRAK Diabetes mellitus merupakan penyakit kronis yang membutuhkan perawatan medis yang lama, dengan cara mengendalikan kadar gula darah untuk terjadinya komplikasi diabetes. Diabetes sering disebut-sebut sebagai ‘ibu’ dari berbagai penyakit. Pasalnya, diabetes bisa menjadi penyebab dari banyak komplikasi penyakit, seperti penyakit jantung, penyakit ginjal, penyakit pada mata, penyakit pada kaki, penyakit saraf, stroke, hipertensi dan masih banyak lagi lainnya. Mengidentifikasi factor-faktor yang berhubungan dengan kejadian diabetes millitus dengan komplikasi hipertensi.  Desain penelitian yang digunakan yaitu Cross Sectional. Populasi  penelitian ini adalah seluruh pasien Diabetes mellitus yang datang berkunjung ke RSUD Sumbersari Bantul Kota Metro dari tanggal 15 Januari-14 Februari 2024. Jumlah sampel sebanyak 40 responden yang ditentukan dengan menggunakan Total Sampling. Uji statistik menggunakan Chi Square (X2).  Penelitian ini menyimpulkan  bahwa ada hubungan yang siqnifikan dan bermakna untuk variabel jenjang pendidikan (p value = 0,007) dan (OR : 16,00), pola konsumsi (p value = 0,035) dan perokok aktif (p value = 0,027) dengan kejadian Diabetes Militus yang mengalami hipertensi, sedangkan yang tidak ada hubungan yang bermakna adalah variable umur, jenis kelamin, indek masa Tubuh, genetic, aktifitas fisik,  dan pola tidur  dengan kejadian Diabetes Militus yang mengalami hipertensi. Kata Kunci: Perokok, Hipertensi, Diabetes Mellitus